Pendidikan Karakter Berbasis Al-Quran - Purnamasari, Dewi (Sekolah Tinggi Agama Islam (STAIN) Curup, 2017)
This article discusses the problem of character education. Character education into the spotlight of attention lately because of the decline, which resulted in the decline of morals. In the Quran, the characters use the term